EXTH-67. IDENTIFICATION AND DEVELOPMENT OF NEURAL ECM-BINDING LAMPREY ANTIBODIES (VARIABLE LYMPHOCYTE RECEPTORS) THAT TARGET GLIOBLASTOMA. (11th November 2019) - Umlauf, Benjamin; Clark, Paul; Lajoie, Jason; Georgieva, Julia; Bremner, Samantha; Herrin, Brantley; Shusta, Eric; Kuo, John
Abstract: INTRODUCTION: The median survival of glioblastoma (GBM) patients remains less than two years even with state-of-the-art treatment. Current targeted GBM therapies demonstrate initial therapeutic benefit; however, patients relapse due to therapeutic selection of treatment resistant GBM cellular populations. Therefore, we propose targeting pathologic disruption of the blood brain barrier (BBB) via exposure of neural ECM, rather than disease markers, to overcome therapy-resistant GBM. METHODS: We identify V ariable L ymphocyte R eceptors (VLRs, the antigen recognition system used by lamprey) that demonstrate high specificity for neural ECM. Candidate VLRs underwent further refinement using in vitro binding assays and ex vivo tissue staining. Utilizing pathologic disruption of BBB as an approach for targeting GBM was confirmed in vivo using intracranial murine glioblastoma models. RESULTS: The lead neural ECM-binding VLR candidate, named P1C10, demonstrates diffuse binding to parenchymal neural ECM, without detectable binding to other tissues. P1C10 demonstrates nanomolar affinity for in vitro derived neural ECM, and preferentially accumulates at intracranial GL261 and U87 lesions in murine GBM models. Finally, administration of P1C10-targeted doxorubicin-loaded liposomes significantly extends the survival of mice bearing intracranial U87 GBM. CONCLUSIONS: We identified VLRs that bind neural ECM, and demonstrate their utility for delivering compounds and nanoparticles to sites of GBM induced blood brain barrier disruption. This novel strategy allows for targeting therapeutics via the underlying physiology of GBM rather than relying on cellular disease markers that are often lost in patients that relapse after targeting therapies.